Diffraction of Torsional Elastic Waves by a Rigid Annular Disc at a Bimaterial Interface - Mandal, S.C.; Gosh, M.L. (Engineering Transactions, 1993)
The problem of diffraction of normally incident torsional wave by an annular rigid disc lying at the interface of two bonded dissimilar semi-infinite elastic media is analysed. The three-part mixed boundary value problem is reduced to the solution of a set of integral equations which are solved by using iterative technique for low frequency, assuming that the ratio of the inner and outer radii is small. The stress distribution on the disc, the torque and far-field amplitudes of the displacement in both the media are evaluated. The variation of dynamic stress intensity factors with normalised frequency for various values of the material parameters, and also the variation in far-field amplitude with the polar angles for a fixed radial distance have been shown by means of graphs.